Complementary use of wearable technology 4: assessing gait asymmetry and shock attenuation using multiple IMU devices - Williams, J. H.; Rizzuto, S. F.; Dillard, B. A.; Whitaker, E. J. (Sport Performance & Science Reports, 2022)
In the previous study (16) we developed procedure to tempo rally synchronize and align data from multiple IMUs. The results showed that accelerometer signals from the IMeasureU Blue Trident sensor (BT-IMU) and STATSports APEX unit can be synchronized and, once synchronized, show consider able similarity. This raises the possibility of coupling raw ac celerometer data generated from the APEX sensor (e.g. speed, trunk acceleration and angular velocity) with data from the BT-IMU (ankle acceleration and angular velocity).